IMMU-16. TWO DISTINCT SUBSETS OF NATURAL KILLER CELLS ARE ENRICHED IN THE TUMOR MICROENVIRONMENT AND CORRELATE WITH SURVIVAL OUTCOME IN HUMAN GLIOBLASTOMA. (9th November 2020) - Bartkowiak, Todd; Barone, Sierra; Hayes, Madeline; Roe, Caroline; Sinnaeve, Justine; Mistry, Akshitkumar; Leelatian, Nalin; Greenplate, Allison; Mobley, Bret; Chambless, Lola; Thompson, Reid; Weaver, Kyle; et al.
Abstract: Glioblastomas (GBM) account for up to 60% of all adult primary brain tumors. With few advances in therapeutics, median overall survival (mOS) remains at 15-months post diagnosis. Success of immunotherapy in peripheral solid tumors may offer an alternative therapeutic approach for patients with GBM tumors; however, no predictive immune features currently inform therapeutic stratification for GBM. Recently, we have identified radiographic tumor contact with the lateral ventricle (LV) as a prognostic indicator of OS, as patients with LV+ GBM survive 7 months less than patients with LV- gliomas. This disparity was independent of known prognostic factors (e.g. KPS, extent of resection). Further, we have identified a correlation between greater immune infiltration and the frequency of tumor subtypes with more favorable prognosis. We therefore hypothesized that differences in overall survival between patients with LV+ and LV- are due, in part, to a uniquely immunosuppressive microenvironment within the LV. Using 35-parameter single-cell mass cytometry (CyTOF) we profiled the immune infiltrate of human GBM tissue acquired in accordance with the Declaration of Helsinki and with the approval of the institutional review board (IRB #131870). Computational approaches (tSNE, Citrus, RAPID) correlated natural killer (NK) cell populations correlating with prognosis. NK cells made of 1–14% of the total immune infiltrate in GBM. Ninety percent of NK cells infiltrating LV- tumors were CD16+CD56dim cytotoxic NK cells (cNK). LV+ gliomas, however, were enriched in CD16+CD56bright immunoregulatory NK cells (irNK). The presence of cNK cells correlated with a 2.5-fold improvement of OS, whereas irNK cells correlated with a 2.2-fold reduction in OS. Further, 30–60% of NK cells infiltrating LV+ tumors expressed checkpoint receptors (TIGIT, TIM3, B7-H3) compared to only 10–20% in LV- tumors. These results suggest that NK cells contribute to immunosuppression in the LV and may serve as alternative targets to T cell-based therapies for GBM.